2017
DOI: 10.1111/1365-2664.12868
|View full text |Cite
|
Sign up to set email alerts
|

Microhabitat heterogeneity and a non‐native avian frugivore drive the population dynamics of an island endemic shrub, Cyrtandra dentata

Abstract: Summary Understanding the role of environmental change in the decline of endangered species is critical for designing scale‐appropriate restoration plans. For locally endemic rare plants on the brink of extinction, frugivory can drastically reduce local recruitment by dispersing seeds away from geographically isolated populations. Dispersal of seeds away from isolated populations can ultimately lead to population decline. For localized endemic plants, fine‐scale changes in microhabitat can further limit popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Such differences could be explained by low seedling recruitment in the liana populations and subsequent lack of change in the number of young individuals over time. It has been cautioned that long‐term elasticity analysis may not always adequately describe the relative importance of vital rate life stage contributions to the short‐term population growth rate (Bialic‐Murphy et al, 2017; Haridas & Tuljapurkar, 2007). Thus, we suggest future research investigating both the short‐ and long‐term elasticity patterns of B. caapi is critical to understanding the population dynamics of lianas and for the development of sound management plans for this culturally and economically important NTFP plant species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such differences could be explained by low seedling recruitment in the liana populations and subsequent lack of change in the number of young individuals over time. It has been cautioned that long‐term elasticity analysis may not always adequately describe the relative importance of vital rate life stage contributions to the short‐term population growth rate (Bialic‐Murphy et al, 2017; Haridas & Tuljapurkar, 2007). Thus, we suggest future research investigating both the short‐ and long‐term elasticity patterns of B. caapi is critical to understanding the population dynamics of lianas and for the development of sound management plans for this culturally and economically important NTFP plant species.…”
Section: Discussionmentioning
confidence: 99%
“…These approaches which are solely based on long‐term projections, may underestimate the short‐term effects of harvest (Gaoue, 2016). Elasticity analyses of short‐term population dynamics are likely critical for the development of robust management plans (Bialic‐Murphy et al, 2017; Gaoue, 2016), especially, for economically important plant species that are harvested under various harvest regimes. Furthermore, understanding the relative contribution of vital rates to differences in population growth rates prospectively and retrospectively will prove informative (Caswell, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we were interested in the role of dispersal among patches and landscape structure on population variation and assumed homogeneous environmental conditions with the patches. We recognize that microhabitat heterogeneity and the consequences of short distance dispersal on demography are important (Bialic‐Murphy, Gaoue, & Kawelo, ; Godínez‐Alvarez & Jordano, ; Loayza & Knight, ), but the analysis of these factors on our focal species is beyond the scope of this work.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that perturbations of earlier life stages are often more important in the transient phase than in the asymptotic phase (Fox and Gurevitch, 2000;McMahon and Metcalf, 2008;Haridas and Gerber, 2010;Miller and Tenhumberg, 2010;Bialic-Murphy et al, 2017). Furthermore, anthropogenic stressors can have a greater negative effect on the short-term population growth rate under more optimal abiotic conditions than less optimal abiotic conditions (Gaoue, 2016).…”
Section: Elasticity Analysismentioning
confidence: 99%
“…The use of short-and long-term population projections to characterize how skewed stage structures influence plant population dynamics over time has become increasingly important for understanding the effects of environmental change on fundamental patterns in ecology. For example, short-and long-term projections have been used to characterize plant population responses to herbivory pressure (Maron et al, 2010), harvesting (Gaoue, 2016), biological invasion (McMahon and Metcalf, 2008;Ezard et al, 2010), severe catastrophic events (Crain et al, 2019), and habitat disturbance (Ezard et al, 2010;Bialic-Murphy et al, 2017). While it is likely that the distinction between short-and long-term dynamics is particularly important for assessing the likely outcome of plant reintroductions with artificially skewed stage structures, there is a dearth of demographic studies on this topic (but see, Wong and Ticktin, 2015).…”
Section: Introductionmentioning
confidence: 99%